Effect of work-rate on synergy of corrosion and wear of nickel-based 690 alloys under fretting conditions - Wenjie Pei; Shengzan Zhang; Mengyuan Ma; Wei Tan; Guorui Zhu (Results in Engineering)
The heat exchange tubes in the secondary steam generator of pressurized water reactor vibrate due to the impact of fluid, which results in collision leading to fretting wear. The work-rate can characterize random vibrations over time. The effect of work-rate under random vibration on the fretting corrosion of nickel-based 690 alloys in high-temperature and high-pressure environments was studied. The work-rate was set at 4, 5, and 6 mW, respectively. Interestingly, the wear volume did not climb up continuously with the increase in work-rate, and declined at 6 mW. SEM and EDX characterization revealed that the wear mechanism changed from abrasive wear and delamination wear to abrasive wear and oxidation wear. Electrochemical analysis and calculations showed that pure wear and corrosion-promoted wear accounted for more than 90 % of the wear damage, while pure corrosion and wear-promoted corrosion accounted for less than 10 %. The synergistic effect was not ignored. Therefore, the reduction in wear at 6 mW is primarily due to the wear debris and small amounts of oxides shed during fretting, which reformed a protective layer on the wear scar under mechanical action. This study has certain cognitive significance for the exploration of corrosion of heat exchange tubes under actual working conditions.